Directional studies in cosmic rays : with particular reference to processes involving mesons. - Fenton, Keith Bryan (1952)
Cosmic ray investigations in Hobart were initiated by my brother Dr. A. G. Fenton in 1946. The problem chosen by him for investigation was the high latitude E-W asymmetry, since it seemed that, during the difficult period of building up a research programme in a field which has attracted many workers in other parts of the norld, useful results might be obtained from the beginning. The first measurements carried out by my brother and Dr. D.W.P. Burbury indicated that an asymmetry existed at Hobart. In 1948, I was able to take an active part in this work. It had become apparent that measurements in a higher geomagnetic latitude would be desirable. My brother and I therefore suggested to the Australian National Antarctic Research Expedition (A.N.A.R.E.) that measurements should be made at the Antarctic Scientific Station on Macquarie Island, which had just been established. We were able to secure a grant from A.N.A.R.E. to construct the necessary equipment for this work.